EFEKTIVITAS MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE, CREATE AND SHARE) BERBASIS LESSON STUDY TERHADAP KETERAMPILAN BERPIKIR KREATIF - Murtini, *Iin; Noviyanti, Nurul Ika; Mukti, Windy Rosyada; Mahanal, Susriyati (Universitas Muhammadiyah Metro, 2023)
Education needs renewal to produce a generation that has skills in accordance with the demands of the 21st century. The purpose of this study was to determine the effectiveness of the lesson study-based SSCS (search, solve, create, and share) learning model on creative thinking skills. This type of research is classroom action research (CAR) combined with lesson study. The research was conducted at the State University of Malang with 30 student subjects. The instruments used in this study were observation sheets, student questionnaires, creative thinking questions, and rubrics. The results of this study indicate that there is a difference between pre-treatment, cycle I, and cycle II, as indicated by F count > F table, or, as it can be said, 3.11 > 3.10, so it can be concluded that the learning model used by the model lecturer is able to improve creative thinking skills